Keabsahan Perkawinan dalam Perspektif Adat Towani Tolotang : Studi di Kabupaten Sidrap Provinsi Sulawesi Selatan - Rukdah Tufatul Ilmi (Jurnal Hukum dan Sosial Politik, 2025)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife whose aim is to form a happy and eternal family (household) based on the belief in the Almighty God. Law 1/1974 refers to the validity of a marriage held by Indonesian citizens based on the laws of their respective religions and beliefs. The aim of this thesis is to analyze the Towani Tolotang Traditional Marriage process in relation to Hindu Religious Marriages and analyze the validity of Towani Tolotang Traditional Marriages Based on Marriage Law in Indonesia. It becomes a problem when a community of Towani Tolotang believers are "forced" to choose Hinduism among the religions recognized by the government, which then relegates their belief to just a custom. The next big question about how the Towani Tolotang Traditional Marriage process relates to Hindu Religious Marriages is how is the validity of the Towani Tolotang Traditional Marriage based on Marriage Law in Indonesia. The research was carried out in Sidrap Regency, Panrenge Telelimpoe Village, Province. South Sulawesi, data collection was obtained using interviews and analyzing data from literature references, either from books or from journals via the internet. After the data obtained has been collected, it will then be discussed and explained in accordance with applicable regulations and the final results will be concluded. The results of the conclusions must be in accordance with the research results from the title "The Validity of Marriage in the Towani Tolotang Traditional Perspective (Study in Sidrap Regency, South Sulawesi Province)", Based on the results of the analysis and interviews regarding Towani Tolotang Traditional Marriage and Hinduism, namely that the procedure or process of marriage what is carried out by the Towani Tolotang Custom is not the same as the provisions of the marriage procedures in Hinduism, furthermore the Towani Tolotang Customary Marriage is declared valid according to the provisions of the Law. Marriage in Indonesia is because the marriage is carried out in accordance with the principles or principles and values ​​contained in Law 1/1974.